1996
DOI: 10.1002/eji.1830261237
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐12 activates human γδ T cells: synergistic effect of tumor necrosis factor‐α

Abstract: gammadelta T cell populations are known to expand in response to intracellular bacterial infectious agents regardless of previous priming. We have shown previously that soluble factor(s) produced by Mycobacterium-stimulated monocytes activate cord blood gammadelta T cells to proliferate. In this study, we investigated whether cytokines produced by monocytes are responsible for gammadelta T cell activation in vitro: interleukin (IL)-1beta, IL-6, IL-8, IL-12, tumor necrosis factor (TNF)-alpha and granulocyte/mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 34 publications
2
41
1
Order By: Relevance
“…In addition to TNF, we also observed a significant increase in the production of IL-12 in the lung. TNF has been shown to enhance IL-12 production from NK and T cells previously (65,66). Given that IL-12 is a potent inducer of IFN-␥, it is quite likely that beneficial effects of adTNF in vivo are in part attributable to activating effects of cytokine networks initiated by TNF.…”
Section: Discussionmentioning
confidence: 95%
“…In addition to TNF, we also observed a significant increase in the production of IL-12 in the lung. TNF has been shown to enhance IL-12 production from NK and T cells previously (65,66). Given that IL-12 is a potent inducer of IFN-␥, it is quite likely that beneficial effects of adTNF in vivo are in part attributable to activating effects of cytokine networks initiated by TNF.…”
Section: Discussionmentioning
confidence: 95%
“…Analysis gate was set as described in Fig. 1 T cell proliferation (53). We have previously reported that ␥␦ T cells proliferate in response to IL-15 in vitro (37,54).…”
Section: Discussionmentioning
confidence: 99%
“…2). In addition, TNF-␣ activates T cells or T-cell subsets, thereby facilitating the generation of cytokines and/or cytotoxic effector molecules and ensuring their sustained expression by the cells (11,30). TNF-␣ also activates and fosters differentiation of dendritic cells for enhanced IL-12 production and antigen presentation (11).…”
Section: Discussionmentioning
confidence: 99%